Dimensões de criatividade matemática manisfestadas por alunos do quinto ano do ensino fundamental na resolução de problemas envolvendo a unidade temática números - VIANA, Maria Neuraildes Gomes (2024)
The research aimed to analyze the mathematical creativity expressed by students in the fifth year of Elementary School, when engaged in activities related to the thematic unit of Numbers, focused on problem-solving. The research began with a bibliographical survey, aiming to support the study, thus grounding its theoretical framework and the research results. The main theoretical foundations that underpinned this research refer to the teaching of Mathematics in the early years, specifically the thematic unit of Numbers and the relationships between creativity and Mathematics teaching, and finally, problem-solving in Mathematics education. This research was qualitative in nature and of the action research type, as it was related to a survey of data on the motivations of a group, whose focus led to the understanding and interpretation of certain behaviors, opinions and expectations on a given subject. The research subjects were students in the fifth year of Elementary School and the respective teacher of the class studied from a public school in the city education network of Bacabeira-MA. The data collection instruments were: application of problems to students; carrying out a questionnaire with the teacher who teaches mathematics in the investigated class; participant observation, with records in a field diary and documentary analysis of the written resolutions of the problems proposed to the students. The study concluded that teaching the theme of Numbers through problem solving provided students with enriching and challenging experiences, which gave them the opportunity to build new mathematical learning, with interaction, socialization and discussion of the strategies used in solving the proposed problems, based in their intuitions and in their prior knowledge. Another perception is that mathematical creativity emerged when they were thinking in different ways, thus producing different resolutions to problems. Therefore, the teacher must value reasoning and the path taken by the student to reach a solution to the problem, even if the answer is not correct, as well as investigate the extent to which creativity can be found in teaching Mathematics.